Tenascin-C in fibrosis in multiple organs: translational implications - Bhattacharya, S; Midwood, KS; Varga, J (Elsevier, 2022)
Systemic sclerosis (SSc, scleroderma) is a complex disease with a pathogenic triad of autoimmunity, vasculopathy, and fibrosis involving the skin and multiple internal organs [1]. Because fibrosis accounts for as much as 45% of all deaths worldwide and appears to be increasing in prevalence [2], understanding its pathogenesis and progression is an urgent scientific challenge. Fibroblasts and myofibroblasts are the key effector cells executing physiologic tissue repair on one hand, and pathological fibrogenesis leading to chronic fibrosing conditions on the other. Recent studies identify innate immune signaling via toll-like receptors (TLRs) as a key driver of persistent fibrotic response in SSc. Repeated injury triggers the in-situ generation of “damage-associated molecular patterns” (DAMPs) or danger signals. Sensing of these danger signals by TLR4 on resident cells elicits potent stimulatory effects on fibrotic gene expression and myofibroblast differentiation triggering the self-limited tissue repair response to self-sustained pathological fibrosis characteristic of SSc. Our unbiased survey for DAMPs associated with SSc identified extracellular matrix glycoprotein tenascin-C as one of the most highly up-regulated ECM proteins in SSc skin and lung biopsies [3,4]. Furthermore, tenascin C is responsible for driving sustained fibroblasts activation, thereby progression of fibrosis [3]. This review summarizes recent studies examining the regulation and complex functional role of tenascin C, presenting tenascin-TLR4 axis in pathological fibrosis, and novel anti-fibrotic approaches targeting their signaling.